Transcriptomic analysis of LMH cells in response to the overexpression of a protein of Eimeria tenella encoded by the locus ETH_00028350 - Wu, Xiao-Jing; Gao, Jin; Mu, Bing-Jin; Yu, Lin-Mei; Wang, Zi-Rui; Zheng, Wen-Bin; Gao, Wen-Wei; Zhu, Xing-Quan; Liu, Qing (Frontiers in Veterinary Science, 2022)
A protein of Eimeria tenella (encoded by the locus ETH_00028350) homologous to Toxoplasma gondii dense granule protein 9, designated as EtHGRA9 hereafter, was reported to be expressed in all life cycle stages of E. tenella. However, no data are currently available regarding its functional properties. In the present study, a recombinant vector harboring a 741 bp gene segment encoding the mature form of EtHGRA9 was constructed and transfected into leghorn male hepatoma (LMH) cells. Then, transcriptomic analysis of the transfected LMH cells was carried out by using a high-throughput RNA-seq technology. The LMH cells overexpressing EtHGRA9 was validated by means of Western blotting as well as indirect immunofluorescence staining. The results demonstrated that the expression of 547 genes (275 upregulated genes and 272 downregulated genes) was altered by EtHGRA9. The quantitative real-time polymerase chain reaction (qRT-PCR) validation of the ten genes with differential expression between the two groups was consistent with the transcriptome analysis. According to pathway enrichment analysis for the obtained differentially expressed genes, seven pathways were significantly affected by EtHGRA9, such as cytokine-cytokine receptor interaction, MAPK signaling pathway, and protein processing in endoplasmic reticulum. Our data reveal several possible roles of EtHGRA9 in immune or inflammatory responses, which paves the way for a better understanding of the molecular interplay between E. tenella and its host.